A Giant Arteriovenous Malformation Involving Tongue, Neck and Face - Khan, Md Saif Ullah; Rahman, Md Mahbubur; Adhikary, Dipal Krishna (University Heart Journal, 2018)
Abstract not available University Heart Journal Vol. 13, No. 1, January 2017; 26-28